A versatile cholera toxin conjugate for neuronal targeting and tracing. Issue 45 (1st May 2020) - Haigh, Jessica L.; Williamson, Daniel J.; Poole, Emma; Guo, Yuan; Zhou, Dejian; Webb, Michael E.; Deuchars, Susan A.; Deuchars, Jim; Turnbull, W. Bruce
Abstract : A novel azido-modified cholera toxin B-subunit has been developed for use in vivo as a neuronal tracer. Abstract : Tracing of neurons plays an essential role in elucidating neural networks in the brain and spinal cord. Cholera toxin B subunit (CTB) is already widely used as a tracer although its use is limited by the need for immunohistochemical detection. A new construct incorporating non-canonical azido amino acids (azido-CTB) offers a novel way to expand the range and flexibility of this neuronal tracer. Azido-CTB can be detected rapidly in vivo following intramuscular tongue injection by 'click' chemistry, eliminating the need for antibodies. Cadmium selenide/zinc sulfide (CdSe/ZnS) core/shell nanoparticles were attached to azido-CTB by strain-promoted alkyne–azide cycloaddition to make a nano-conjugate. Following tongue injections the complex was detected in vivo in the brainstem by light microscopy and electron microscopy via silver enhancement. This method does not require membrane permeabilization and so ultrastructure is maintained. Azido-CTB offers new possibilities to enhance the utility of CTB as a neuronal tracer and delivery vehicle by modification using 'click' chemistry.